Pathotyping the zoonotic pathogen streptococcus suis: Novel genetic markers to differentiate invasive disease-associated isolates from non-disease-associated isolates from England and Wales - Wileman,TM; Weinert,LA; Howell,KJ; Wang,J; Peters,SE; Williamson,SM; Wells,JM; Langford,PR; Rycroft,AN; Wren,BW; Maskell,DJ; Tucker,AW; et al. (Journal of Clinical Microbiology, 2019)
Streptococcus suis is one of the most important zoonotic bacterial pathogens of pigs, causing significant economic losses to the global swine industry. S. suis is also a very successful colonizer of mucosal surfaces, and commensal strains can be found in almost all pig populations worldwide, making detection of the S. suis species in asymptomatic carrier herds of little practical value in predicting the likelihood of future clinical relevance. The value of future molecular tools for surveillance and preventative health management lies in the detection of strains that genetically have increased potential to cause disease in presently healthy animals. Here we describe the use of genome-wide association studies to identify genetic markers associated with the observed clinical phenotypes (i) invasive disease and (ii) asymptomatic carriage on the palatine tonsils of pigs on UK farms. Subsequently, we designed a multiplex PCR to target three genetic markers that differentiated 115 S. suis isolates into disease-associated and non-disease-associated groups, that performed with a sensitivity of 0.91, a specificity of 0.79, a negative predictive value of 0.91, and a positive predictive value of 0.79 in comparison to observed clinical phenotypes. We describe evaluation of our pathotyping tool, using an out-of-sample collection of 50 previously uncharacterized S. suis isolates, in comparison to existing methods used to characterize and subtype S. suis isolates. In doing so, we show our pathotyping approach to be a competitive method to characterize S. suis isolates recovered from pigs on UK farms and one that can easily be updated to incorporate global strain collections.